Classical geometry Euclidean, transformational, inversive, and projective - Leonard, I. Ed. 1938-; Lewis, J. E. (James Edward); Liu, A. C. F. (Andrew Chiang-Fung); Tokarsky, G. W. (Hoboken, New Jersey Wiley, 2014)
"Written by well-known mathematical problem solvers, Modern Geometry features up-to-date and applicable coverage of the wide spectrum of modern geometry and aids readers in learning the art of logical reasoning, modeling, and proof. With its reader-friendly approach, this undergraduate text features: self-contained coverage of modern geometry, provides a large selection of solved exercises to aid in reader comprehension, contains material that can be tailored for a one-, two-, or three-semester sequence, and provides a wide range of fully worked exercises throughout"--Provided by publisher.
Includes bibliographical references (pages 467-471) and index.
Keywords: Geometry